Efficacy and safety of nanohybrids comprising silver nanoparticles and silicate clay for controlling Salmonella infection - Bau IJ (Dove Medical Press, 2012)
Shu-Her Chiao,1* Siou-Hong Lin,1* Ching-I Shen,2* Jiunn-Wang Liao,3 I-Jiuan Bau,1 Jiun-Chiou Wei,4 Li-Ping Tseng,1 Shan-hui Hsu,4 Ping-Shan Lai,2 Shinn-Zong Lin,5–7 Jiang-Jen Lin,4 Hong-Lin Su,1,8 1Department of Life Sciences, Agricultural Biotechnology Center, National Chung Hsing University, 2Department of Chemistry, Agricultural Biotechnology Center, National Chung Hsing University, 3Graduate Institute of Veterinary Pathobiology, Agricultural Biotechnology Center, National Chung Hsing University, Taichung, Taiwan; 4Institute of Polymer Science and Engineering, National Taiwan University, Taipei, Taiwan; 5Center for Neuropsychiatry, China Medical University and Hospital, Taichung, Taiwan; 6Department of Neurosurgery, China Medical University Beigan Hospital, Yunlin, Taiwan; 7Graduate Institute of Immunology, China Medical University, Taichung, Taiwan; 8Department of Physical Therapy, China Medical University, Taichung, Taiwan*These three authors contributed equallyAbstract: Developing effective and safe drugs is imperative for replacing antibiotics and controlling multidrug-resistant microbes. Nanoscale silicate platelet (NSP) and its nanohybrid, silver nanoparticle/NSP (AgNP/NSP), have been developed, and the nanohybrids show a strong and general antibacterial activity in vitro. Here, their efficacy for protecting Salmonella-infected chicks from fatality and septicemia was evaluated. Both orally administrated NSP and AgNP/NSP, but not AgNPs alone, effectively reduced the systemic Salmonella infection and mortality. In addition, quantitative Ag analyses demonstrated that Ag deposition from AgNP/NSP in the intestines was less than that from conventional AgNPs, indicating that the presence of NSP for immobilizing AgNPs reduced Ag accumulation in tissue and improved the safety of AgNPs. These in vivo results illustrated that both NSP and AgNP/NSP nanohybrid represent potential agents for controlling enteric bacterial infections.Keywords: silver, nanoparticle, biocompatibility, infection, cytotoxicity